Jiggers Detrimental To Pupils’ Outdoor Play Activities - Makena, Beatrice; Kang’ethe, Dr. Rachel W Kamau (Advances in Social Sciences Research Journal, 2016)
This study intended to investigate the relationship between jigger infestation and participation at school by pre-primary and lower primary school children. The study was carried out in Gatundu South sub-county, which is one of the highly jigger infested zones in Kiambu County, Kenya. The specific objective of this study was to find out the level of participation in outdoor activity by pupils who were infested with jiggers. The Ecological systems theory was utilized and the descriptive survey design was employed. The population of the study comprised of pre-primary, lower primary school children and their class teachers from all the public schools in Gatundu South Sub-County. The sample size was eleven schools. Purposive sampling technique was applied to sample 44 jigger infested children in these schools. Forty-four pupils who were not infested were randomly sampled to be compared with those who were infested. The teachers handling pre-primary school and lower primary classes were also purposively sampled. Data was collected through the use of questionnaires for teachers, observations and document analysis. Qualitative and quantitative methods of data analysis were applied. The Statistical Package for Social Sciences (SPSS) was used to prepare and organize data for analysis. Pearson’s correlation coefficient test was used to compute the relationship between the variables. Frequency distribution tables, percentages, and descriptions were utilized for data presentations. The study concluded that jiggers were a health hazard to the realization of pupils’ outdoor activities. The Pearson correlation coefficient indicated that jiggers significantly affected children’s play in outdoor activities at r =0.306 p = 0.043, n = 44. The study recommended that school managers liaise with health officials to treat those infested, carry out routine checkups on pupils and sensitize communities on the causes, dangers and preventive measures of the jigger parasite in order to help all children realize their full educational potential in life and especially in play because it enhances mental stimulation in children.